Screening Flavonoids for Inhibition of Acetylcholinesterase Identified Baicalein as the Most Potent Inhibitor - Azize Balkis; Khoa Tran; Yan Zhi Lee; Ken Ng (2015)
Screening phenolic and polyphenolic compounds for inhibitory activity against electric eels acetylcholinesterase (AChE) identified baicalein, a major flavone derived from the roots of Scutellaria baicalensis, as the most potent inhibitor with IC50 (concentration required for 50% inhibition) of 0.61 µM. None of the hydroxybenzoic and hydroxycinnamic acids screened showed inhibitory activity measured at 100 µM. Structure-activity relationships based on IC50 values of the active flavonoids showed that inhibitory activity (a) required the unsaturated 2-phenyl-chroman structure, (b) has strong requirement for the A-ring A5-OH, A6-OH and A7-OH groups (b) does not depend on B-ring hydroxyl groups, and (d) was reduced by bulky sugar substitution of the saturated C-ring C3-OH. Enzyme kinetic analysis showed that baicalein is a mixed inhibitor of AChE with K1 (equilibrium constant of dissociation of the inhibitor bound enzyme complex) and K2 (equilibrium constant of dissociation of the inhibitor bound enzyme-substrate complex) of 0.91 and 1.98 µM, respectively.